The Effect of GNS3-Based Virtual Laboratory on Dynamic Routing Configuration Competency of Vocational High School - Aisyah Maydina; Nurul Fahira S; Nurul Fatimah Mas'ud; Nurul Istiqamah; Nurul Izzati Inayah; Nurul Janna (Jurusan Teknik Informatika dan Komputer, 2025)
This study aims to examine the effect of a GNS3-based virtual laboratory on students’ competency in dynamic routing configuration in a Vocational High School Computer and Network Engineering program. The study addresses the limited availability of physical networking devices in vocational schools, which often constrains students’ practical skills development. A quasi-experimental design using a pretest–posttest control group approach was employed. The participants consisted of 64 eleventh-grade students divided into an experimental group (n = 32) and a control group (n = 32). The experimental group received instruction using GNS3 virtual lab simulations, while the control group used conventional teaching methods with limited hardware practice. Data were collected through a validated performance-based test measuring routing configuration skills (RIP and OSPF). Independent sample t-test analysis revealed a statistically significant difference between the posttest scores of the experimental and control groups (p < 0.05). The experimental group achieved a higher mean score (M = 85.47) compared to the control group (M = 74.12). The findings indicate that the GNS3 virtual laboratory significantly improves students’ dynamic routing configuration competency. However, limitations include short intervention duration and single-school sampling. The study contributes to vocational education by providing empirical evidence supporting simulation-based learning integration in networking instruction.